2016
DOI: 10.1007/s11095-016-1952-y
|View full text |Cite
|
Sign up to set email alerts
|

Humid Heat Autoclaving of Hybrid Nanoparticles Achieved by Decreased Nanoparticle Concentration and Improved Nanoparticle Stability Using Medium Chain Triglycerides as a Modifier

Abstract: Incorporation of high amount of MCT changed the morphology of PEG-b-PCL based nanoparticles to an emulsion-like structure and the nanoparticles prepared could withstand autoclaving due to improved particle stability and decreased particle concentration caused by MCT incorporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The solubility data shows that all of these oils could meet the DL requirements of 2.0 mg/mL. S SO , S MCT , S (MCT:SO 1:9) , S (MCT:SO 1:1) , and S (MCT:SO 9:1) were found to be 30.26 ± 0.32 mg/mL, 166.83 ± 12.86 mg/mL, 166.86 ± 35.51 mg/mL, 146.22 ± 15.67 mg/mL, and 173.21 ± 15.13 mg/mL, respectively, confirming previous reports that MCT could improve DL (Gou et al., 2016 ). In addition, MCT could modulate the stability of lipid membranes and their resistance to peroxidation (Anez-Bustillos et al., 2016 ; Luo et al., 2019 ).…”
Section: Resultssupporting
confidence: 88%
“…The solubility data shows that all of these oils could meet the DL requirements of 2.0 mg/mL. S SO , S MCT , S (MCT:SO 1:9) , S (MCT:SO 1:1) , and S (MCT:SO 9:1) were found to be 30.26 ± 0.32 mg/mL, 166.83 ± 12.86 mg/mL, 166.86 ± 35.51 mg/mL, 146.22 ± 15.67 mg/mL, and 173.21 ± 15.13 mg/mL, respectively, confirming previous reports that MCT could improve DL (Gou et al., 2016 ). In addition, MCT could modulate the stability of lipid membranes and their resistance to peroxidation (Anez-Bustillos et al., 2016 ; Luo et al., 2019 ).…”
Section: Resultssupporting
confidence: 88%
“…Phase separation is a common phenomenon that occurs when different nonmiscible substances are blended. According to our previous studies, 17,27 lipids with shorter hydrocarbon chains are more compatible with PCL than the SL used in this study, and thus a higher lipid ratio needs to be reached before phase separation occurs. In this case, due to the stronger intermolecular forces between the long hydrocarbon chains of SL molecules, the SL was found to induce phase separation at relatively lower SL-PCL ratios (Figure 1, Figure 2, B3).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that block copolymers in lipid− PCL mixed nanoparticles with nonhomogeneous cores exhibit better chemical stability in aqueous medium. 27 In this study, incorporation of SL also exhibited a block copolymer stabilizing effect, and the reason for this stabilizing effect was attributed to a decreased core polarity induced by incorporation of SL. As shown in Scheme 1A, there is less accessibility of H + or enzymes into the deeper regions of the core in SL10%-NPs, whereas the chance of H + or enzyme infiltration into the core of NPs is higher due to their higher core polarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations